2017
DOI: 10.1097/pgp.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of HER-2 Gene Amplification and Protein Expression in Benign, Borderline, and Malignant Ovarian Serous and Mucinous Neoplasms

Abstract: Amplification of HER-2 gene and overexpression of HER-2 receptor play a significant role in the progression of a number of malignancies such as breast cancer. Trastuzumab (anti-HER-2 therapeutic agent) has been used successfully in treatment of breast cancer. The aim of this study was to assess the pattern of HER-2 gene amplification and of HER-2 receptor expression in a spectrum of serous and mucinous ovarian tumors to determine whether HER-2 is altered in these neoplasms similar to that occurring in breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Woo et al (17) found HER2 gene amplification by FISH (defined as HER2/CEP17 ratio ≥ 2) in 1 of 31 serous carcinomas arising from fallopian tube/ovary; interestingly that case was scored as 0 on IHC. Mohammed et al (19) showed HER2 protein overexpression (3+ on IHC) in 1 of 53 ovarian serous carcinomas which did not show HER2 gene amplification (defined as ≥ 6 spots/cell) by chromogenic in situ hybridization. In a multi-center study on HER2 status in ovarian carcinomas, Tuefferd et al (7) used slightly different criteria for HER2 gene amplification FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Woo et al (17) found HER2 gene amplification by FISH (defined as HER2/CEP17 ratio ≥ 2) in 1 of 31 serous carcinomas arising from fallopian tube/ovary; interestingly that case was scored as 0 on IHC. Mohammed et al (19) showed HER2 protein overexpression (3+ on IHC) in 1 of 53 ovarian serous carcinomas which did not show HER2 gene amplification (defined as ≥ 6 spots/cell) by chromogenic in situ hybridization. In a multi-center study on HER2 status in ovarian carcinomas, Tuefferd et al (7) used slightly different criteria for HER2 gene amplification FIG.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 is a proto-oncogene which encodes a transmembrane glycoprotein, and its over-expression is involved in the regulation of abnormal proliferation, differentiation and anti-apoptotic processes [12][13]. The HER2 gene is over-expressed in many malignant tumors [14] and trastuzumab, which targets HER2, has been successfully used in the treatment of metastatic breast cancer with HER2-overexpression [15].There has been recent study on HER2 expression in ovarian cancer and its relationship with prognosis [16], and some researchers have found that HER2 gene expression has a key role in the occurrence and development of epithelial ovarian cancer; with the 5-year survival rate of patients with HER2 over-expression significantly decreased [17], suggesting it might be used as a poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that positive HER2 protein was not detected in normal or benign tumor. Borderline tumors show HER2 positive staining, but mostly no overexpression [16] . Chromogenic in situ hybridization (CISH) analysis was calculated from 20 tumor cell nucleus with ratio of HER2/CEP17 (cystadenoma) and HER2/Cen17 (pseudomyxoma).…”
Section: Case Descriptionmentioning
confidence: 99%